The impact of regular yoga practice on the course of endocrinological and diabetological disorders - a literature review. - Ślusarczyk, Monika; Foryś, Angelika; Kwaśniak, Ksenia; Banach, Mariola; Magierska, Agata; Miłek , Magdalena; Stawska, Weronika; Niemczyk, Anna; Kotowicz, Zuzanna; Kmiotek, Weronika (Quality in Sport, 2024)
Introduction and purpose: Yoga originates from ancient Indian culture. Its practice includes asanas (yoga poses) and relaxation (shavasana). An important element of yoga is breath control. It can also be practiced by individuals who are not adapted for physical activity. Numerous studies have proven the positive impact of yoga on various disorders. The aim of this study is to outline the role of yoga in the treatment of diseases with underlying endocrinological disorders: polycystic ovary syndrome, hypothyroidism, and type 2 diabetes. Brief description of the state of knowledge: The growing interest in yoga practice has led to many studies evaluating the impact of regular yoga training on normalizing abnormal hormone levels, metabolic parameters, anthropometric measurements, as well as reducing clinical symptoms of a particular disease. The importance of yoga practice in improving the respiratory and circulatory system functions, regulating menstrual cycles, and ultimately - improving mental health, has also been the subject of research among endocrine patients. Their results suggest a positive impact of regular yoga training on many aspects of endocrine diseases and its advantage over conventional forms of physical activity. Summary: Regular practice of yoga is beneficial as an additional element of therapy for endocrine diseases. It has an impact not only on the regulation of hormonal disorders or anthropometric parameters, but also on improving the mental state, which is often disturbed in endocrine patients. It is worth considering this form of physical activity instead of standard exercises, taking into account its additional benefits.